The National Geographic maps every foldout map from National Geographic magazine on CD-ROM. - National Geographic Society (U.S.). (Washington, D.C. : National Geographic Society, 1998)
Includes National Geographic Magazine maps, 1888-Nov. 1959, and its later title, National Geographic, Dec. 1959-1997. Interactive map tours and time lines introduce the user to a rich collection of more than 500 maps.
Title for container.
System requirements: Windows 95 or Windows 98; 486/66 MHz or faster processor; 16 MB RAM; 40 MB free space; SVGA video card supporting 256 colors; 16 bit sound card and speakers; 2x CD-ROM drive.
System requirements: Macintosh; 68030 33 MHz processor; System 7.5 or higher; 16 MB RAM; 40MB free disc space; 640X480 resolution x 256 colors; 2x CD-ROM drive
Keywords: National Geographic Society (U.S.).; Geography -- Databases; Interactive multimedia; CD-ROMs.